Preparation and Application of Magnetic Fe3O4-SBA-15 Mesoporous Silica Adsorbents - Yang, Shengyun; Yao, Gang (Asian Journal of Chemistry, 2015)
Magnetic Fe3O4-SBA-15 mesoporous silica molecular sieves were prepared, characterized and used as sorbent for magnetic separation and recycle. Powder X-ray diffraction data indicated that the structure of Fe3O4-SBA-15 retained the host SBA-15 structure and Brunauer-Emmett-Teller analysis revealed a increase in surface area and pore size, indicating Fe3O4-SBA-15 mixing with the host SBA-15. From scanning electron micrographs, it was found that the structure of the Fe3O4-SBA-15 particles changed with the content of Fe3O4 and SiO2. And the Fe3O4-SBA-15 exhibited strong magnetic properties. The iron content in Fe3O4-SBA-15 was determined by atom adsorption spectroscopy, with the Fe3O4 content increased, the capacity of adsorption decreased, but the quality of Fe3O4-SBA-15 recycled increased, so we must be controlled the proportion of Fe and Si of Fe3O4-SBA-15 mesoporous material, then we could obtain the better material. Fe3O4-SBA-15 was successfully used for absorb phenol and recover in water. Our results suggest wide applicability of Fe3O4-SBA-15 magnetic mesoporous materials for absorption various compounds in water and recover.